Gaza Reconstruction Post 2014 Aggression Assessing the Role of Municipal Development and Lending Fund (MDLF) - Al-Smairy, Ibtissam Ali Al-Smairy; Migdad, Samah Mohammad; El-Mougher, Mohammed M.; El-Agha, Mohamed Ramadan (Journal of Risk and Crisis Management, 2019)
Due to on-going de-development, the Gaza strip was found to be “uninhabitable” by the year 2020. According to United Nations report, being one of the most densely populated areas on earth, and being a conflict zone in addition to having high poverty rates, Gaza is a target field for International non-governmental organizations (INGOs) as well as for community based organizations (CBOs), specifically in the aftermath of the last conflict 2014 when efforts were geared towards reconstruction and rehabilitation programs. This paper is going to assess the role of the Municipal Development and Lending Fund (MDLF) in the reconstruction and rehabilitation operations in the Gaza strip post 2014 conflict, clarifying how this institution was an important pillar in the recovery process, the author used the personal interview as a tool for data and used the descriptive methodology, as a conclusion there is no permanent plan from the MDLF for emergency situations, this paper recommends more governmental support for funding recovery programs.
Keywords: Reconstruction; Early Recovery; Municipality; Gaza Strip